The neoadjuvant esophageal score: a prognostic tool for predicting survival and postoperative complications in esophageal squamous cell carcinoma - Chen, Hao; Huang, Xuan; Huang, Cheng; Xie, Qichang; Chen, Chun; Zheng, Bin; Lin, Yuxing; Huang, Renjie; Cheng, Li; Yang, Zhang; Xu, Chi (Frontiers in Immunology, 2026)
BackgroundEsophageal squamous cell carcinoma (ESCC) remains a major global health challenge, and reliable prognostic markers. We developed and validated the Neoadjuvant Esophageal (NAE) score, derived from treatment response, to predict overall survival (OS) and postoperative complications in locally advanced ESCC.MethodsWe retrospectively analyzed 411 patients with ESCC from four hospitals who underwent esophagectomy following neoadjuvant therapy between July 2013 and November 2020. Patients were stratified into low-, intermediate-, and high-score groups. OS was assessed using Kaplan–Meier and Cox regression analyses, and predictive models were constructed with nomograms. Model performance was evaluated using concordance index (C-index), ROC curves, calibration plots, and decision curve analysis.ResultsThe NAE score effectively stratified survival outcomes (5-year OS, p < 0.001), with higher scores indicating worse prognosis. Adjuvant therapy provided a significant OS benefit only in the high-NAE group (p = 0.044), but not in the low- or intermediate-score groups. Multivariable Cox analysis confirmed the NAE score, perineural invasion, lymphovascular invasion, and neutrophil count as independent prognostic factors. A survival nomogram incorporating these variables demonstrated strong discrimination (C-index=0.742) and superior predictive accuracy compared with TNM staging (AUC 0.673–0.835 vs. 0.618–0.725). In addition, a complication-prediction nomogram integrating NAE score, surgical approach, and alcohol consumption reliably predicted major postoperative complications (C-index=0.789).ConclusionThe NAE score is a robust prognostic tool for patients with locally advanced ESCC, capable of predicting survival, guiding adjuvant therapy, and estimating risk of severe postoperative complications. Its integration into clinical practice could refine risk stratification and support personalized treatment strategies, with prospective validation warranted.